Основная проблематика социолингвистических исследований - Исаев, Э.Ш. (Культура народов Причерноморья, 2003)
The main problems of stylistic investigations are discovered in the article. The structure of social differentiation of the language is analyzed from the point of view of the stratification and situational differentiation. The studying of situational differentiation is specific interest.